2015
DOI: 10.1128/cmr.00124-14
|View full text |Cite
|
Sign up to set email alerts
|

A Microbiological Revolution Meets an Ancient Disease: Improving the Management of Tuberculosis with Genomics

Abstract: SUMMARY Tuberculosis (TB) is an ancient disease with an enormous global impact. Despite declining global incidence, the diagnosis, phenotyping, and epidemiological investigation of TB require significant clinical microbiology laboratory resources. Current methods for the detection and characterization of Mycobacterium tuberculosis consist of a series of laboratory tests varying in speed and performance, each of which yields incremental information about the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 102 publications
(149 reference statements)
0
31
0
Order By: Relevance
“…When the same strains that were subjected to WGS were examined by traditional methods, they were, in part, wrongly clustered. By disclosing superspreaders, WGS allows prediction of undiagnosed cases and therefore early administration of proper treatment to newly infected individuals (55-57, 215,228,229). However, it was also observed that strains that were clustered by WGS were not necessarily linked by patient interview data.…”
Section: Methods Based On Nonrepetitive Sequencesmentioning
confidence: 97%
“…When the same strains that were subjected to WGS were examined by traditional methods, they were, in part, wrongly clustered. By disclosing superspreaders, WGS allows prediction of undiagnosed cases and therefore early administration of proper treatment to newly infected individuals (55-57, 215,228,229). However, it was also observed that strains that were clustered by WGS were not necessarily linked by patient interview data.…”
Section: Methods Based On Nonrepetitive Sequencesmentioning
confidence: 97%
“…Chief amongst these is that just as early MTB genomic efforts led to new molecular diagnostic tools based on a handful of sequenced genomes [9], the generation and sharing of thousands of MTB genomes will likely lead to new molecular tools for use in higher-incidence settings. Genomics is stimulating TB research and reinvigorating a community that has experienced de-prioritisation (area 1), potentially leading to renewed political interest in TB control and the specialised training and creation of central repositories.…”
Section: To the Editormentioning
confidence: 99%
“…We applaud this framework and the recognition that elimination in low-incidence countries is a unique problem, where infection occurs amongst the most difficult-to-reach individuals. Although "new research and tools" is one of the framework's areas, it overlooks an important new technology that is changing our understanding of TB and our approaches to diagnosis, phenotyping, and treatment -whole genome sequencing (WGS) of Mycobacterium tuberculosis (MTB) isolates from cases of active TB [3,4].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…migrants) also [1,8]. Within the spirit of the new WHO End TB Strategy and the perspective to achieve TB elimination the different stakeholders (including donors and scientific societies) need to collaborate in promoting the translational research activities necessary to improve diagnostic and treatment tools available for TB patients and their families [9]. Linezolid in drug-resistant tuberculosis: haste makes waste…”
Section: From the Authorsmentioning
confidence: 99%